Thermoregulatory responses to constant versus variable-intensity exercise in the heat - Mora-Rodriguez, R.; Del Coso, J.; Estevez, E. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To compare the thermoregulatory responses between constant (CON) and variable-intensity exercise (VAR) in a dry-hot environment (36°C, 29% relative humidity, and 2.5 m/s airflow).